New Working Documents (2) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Desk Study on Land-use Management in Sub-Saharan Africa. M van de Sand. CTA. 1999. 18 pp. CTA number 8012. 5 credit points